Sérialité et réflexivité : les suites conscientes d’elles-mêmes - Jules Sandeau (Mise au Point)
This article studies the manner in which some serial contemporary productions problematize their sequel status within their diegesis. The examination of the different metadiscursive strategies that these sequels have recourse to in order to exorcise the suspicion of illegitimacy that haunts them leads us to identify three main aspects of this reflexive posture. Each modality is successively studied in depth through the analysis of a film that embodies an emblematic expression of it (Scream 4, 22 Jump Street, Jurassic World).